Las medidas correctivas en los procedimientos administrativos sancionadores de las municipalidades. Un ajuste necesario de legalidad. - Pando Vilchez, Jorge Manuel (2021)
This article analyzes the regulation that corrective measures have in the administrative sanctioning procedures of municipalities, by taking as a reference diverse municipal ordinances on the matter. The author identifies how those measures are framed or not in the general regulation of the administrative sanctioning procedure established by the Peruvian Law of the General Administrative Procedure or the Organic Municipality Law and what shall be corrected or not on the matter in current municipality regulation.